1990
DOI: 10.1121/1.399551
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion analysis of acoustic velocities in rocks

Abstract: Acoustic velocity dispersions in three rocks saturated with water, normal decane (n-decane), and a heavy oil (in petroleum engineering, heavy oil is referred to as crude oil with viscosity higher than 0.5 Pa s), respectively, are calculated in this paper. The results show that the apparent velocity dispersion in light fluid (low-viscosity)-saturated rocks is relatively small, usually less than 3% to 5%, whereas that in the same rocks saturated with heavy oil is much larger. Such apparent velocity dispersion ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…The measurements all were taken at constant in-situ pressures and the measured velocities were directly coupled to the changes of the saturating fl uids, providing a good chance to investigate the effect of fl uid viscosity on velocity dispersion. The primary characteristics of the measured dispersion in saturated sandstones with varying fluid viscosity were consistent with previous studies (e.g., Winkler, 1985;Wang and Nur, 1990;Dvorkin et al, 1995;Batzle et al, 2001;Deng et al, 2003; and can be interpreted by two mechanisms of solid/fl uid interaction: the Biot mechanism of large scale average motion of the fl uid phase relative to the solid phase (inertial coupling) and the squirt-flow mechanism of grain-scale relative motion. Both theoretical concepts have a viscositydependent characteristic frequency, which roughly is the boundary between high and low frequency range.…”
Section: Fig 3 the Variations Of The Fl Uid Mobility (K/η) Versus Thsupporting
confidence: 69%
See 1 more Smart Citation
“…The measurements all were taken at constant in-situ pressures and the measured velocities were directly coupled to the changes of the saturating fl uids, providing a good chance to investigate the effect of fl uid viscosity on velocity dispersion. The primary characteristics of the measured dispersion in saturated sandstones with varying fluid viscosity were consistent with previous studies (e.g., Winkler, 1985;Wang and Nur, 1990;Dvorkin et al, 1995;Batzle et al, 2001;Deng et al, 2003; and can be interpreted by two mechanisms of solid/fl uid interaction: the Biot mechanism of large scale average motion of the fl uid phase relative to the solid phase (inertial coupling) and the squirt-flow mechanism of grain-scale relative motion. Both theoretical concepts have a viscositydependent characteristic frequency, which roughly is the boundary between high and low frequency range.…”
Section: Fig 3 the Variations Of The Fl Uid Mobility (K/η) Versus Thsupporting
confidence: 69%
“…For the past several decades, considerable efforts have been made to quantitatively understand and separate the mechanisms producing velocity dispersion (e.g., Wang and Nur, 1990;Dvorkin and Nur, 1993;Parra, 2000;Yang and Zhang, 2002;Ba et al, 2008;Wei et al, 2008;Nie et al, 2010). Although the velocity dispersion is subject to the joint effects of pore structure, fluid property, pressure, temperature, clay content, heterogeneity, and etc., the amount and position of velocity dispersion of reservoir rocks are strongly associated with fluid mobility in the pores, of which the fluid viscosity is one important factor but it works theoretically differently in the two most important mechanisms that are generally accepted for interpreting fluid induced dispersion in saturated rocks: the Biot flow mechanism of large scale average motion of the fl uid phase relative to the solid phase (Biot, 1956) and the local flow or squirt flow mechanism of grain-scale relative motion (e.g., Mavko and Nur, 1975;O'Connell and Budiansky, 1977;Murphy, 1984;Winkler, 1985Winkler, , 1986Mavko and Jizba, 1991;Dvorkin et al, 1994;Dvorkin et al, 1995;Batzle et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it is well known that the Biot theory cannot adequately explain the large velocity dispersion and the strong attenuation in many rocks. Many investigators have shown that the squirt-flow mechanism can be responsible for the observed large attenuation and velocity dispersion [3,[5][6][7]. Dvorkin and Nur [1], Dvorkin et al [2,8] have also shown that the squirt-flow mechanism results in much higher and realistic attenuation in saturated rocks than that predicted by the Biot mechanism.…”
Section: Introductionmentioning
confidence: 89%
“…The velocity deviation log, which is calculated by combining the sonic log with the neutron or density log, provides a tool to obtain well information on the predominant pore type in carbonates [Wang and Nur, 1990]. Velocity deviation characterizes with three zones.…”
Section: Velocity Deviation Logmentioning
confidence: 99%